Building a Core Value-Based Organizational Culture in Christian Higher Education: a Study at Toraja Christian University - Pasoloran, Oktavianus; Matasik, Ade Lisa (Jurnal Ekonomi, 2025)
The purpose of this study is to determine how to build a Christian university organizational culture based on core values. This study uses a qualitative approach with a case study method focused on a university, namely Universitas Kristen Indonesia Toraja. The research data was obtained through observation and interview instruments. The data analysis technique used was thematic analysis through coding of interview transcripts or observation notes. This study emphasizes that the core values formulated by UKI Toraja are not only important in determining the organization's direction but also serve as guidelines and guidance for all university stakeholders. More transcendental values, such as Christianity, local wisdom philosophy, human dignity, as well as social and national concern, require critical reflection that enables every member of the UKI Toraja community to be directed toward the same goal. Core values ultimately build organizational cultural values as pillars of transformation in facing the challenges of changes in the higher education environment and enhancing more meaningful commitment from the entire academic community.